1993
DOI: 10.2307/1591658
|View full text |Cite
|
Sign up to set email alerts
|

Avian Eimeria: Effects of Gamma Irradiation on Development of Cross-Species Immunity in Foreign and Natural Host Birds

Abstract: Repeated inoculation (immunization) of white leghorn chickens with oocysts of the turkey coccidium, Eimeria adenoeides, resulted in significantly improved weight gain and feed-conversion ratios (feed efficiency) after E. tenella challenge. However, the development E. tenella in the immunized chickens did not differ markedly from that in unimmunized chickens, and intestinal lesions remained severe (greater than 3.0). Apparently improved weight gain and feed efficiency can be maintained in the presence of extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Jenkins et al (1991a) used X-irradiated oocysts of E. acervulina to produce a vaccine conferring resistance against coccidiosis and suggested that protective immune responses of the host occurred during an early critical period in intracellular development. Repeated inoculation with ␥-irradiated turkey coccidium (E. adenoides) into chickens resulted in significantly improved weight gain and feed efficiency after challenge with E. tenella (Augustine et al, 1993). In this foreign host, E. adenoides sporozoites excysted and invaded the intestinal epithelium but underwent little or no further development.…”
Section: Attenuated Vaccines Against Eimeriamentioning
confidence: 99%
“…Jenkins et al (1991a) used X-irradiated oocysts of E. acervulina to produce a vaccine conferring resistance against coccidiosis and suggested that protective immune responses of the host occurred during an early critical period in intracellular development. Repeated inoculation with ␥-irradiated turkey coccidium (E. adenoides) into chickens resulted in significantly improved weight gain and feed efficiency after challenge with E. tenella (Augustine et al, 1993). In this foreign host, E. adenoides sporozoites excysted and invaded the intestinal epithelium but underwent little or no further development.…”
Section: Attenuated Vaccines Against Eimeriamentioning
confidence: 99%